Megalyra baltica Poinar and Shaw n. sp. (Hymenoptera: Megalyridae), a long-tailed wasp from Baltic amber - Poinar, George; Shaw, Scott Richard (Zootaxa, 2007)
The wasp family Megalyridae includes eight living genera of presumed idiobiont ectoparasitoids, most of which are associated with relict primary tropical forests (Shaw 1990b, 2006). Their biology is poorly known except for a few species. Their behavior and host range appear to be diverse since one Australian species, Megalyra fasciipennis Westwood, parasitizes cerambycid beetle larvae in wood, while the much smaller Australian M. troglodytes Naumann parasitizes sphecid wasp larvae in mud nests on vertical rock faces (Shaw 1990a). The long ovipositor of many Megalyra species, as well as the phylogenetic analysis of Shaw (1990b), suggests that parasitism of immature wood-boring beetles is the ancestral and more generalized behavior for the genus. It is presumed that ancient megalyrids, like many of their modern descendants, would have been attracted to dead and dying beetle-infested trees, where they might become trapped in sap flows, and eventually fossilized as amber inclusions.